Maternal and umbilical cord blood levels of leptin in pre-eclamptic and healthy pregnant women: A comparative cross-sectional study - Lazarus Ugochukwu Okafor; George Uchenna Eleje; Joseph Ifeanyichukwu Ikechebelu; Emmanuel Onyebuchi Ugwu; Obi Betrand Nwosu; Okechukwu Christian Ikpeze; Gerald Okanandu Udigwe; Ahizechukwu Chigoziem Eke; Samuel A Okoli; Charlotte Blanche Oguejiofor; Chukwudi Anthony Ogabido; Divinefavour Echezona Malachy; et al. (Women's Health, 2023)
Background: Pre-eclampsia is a multi-systemic disease with its attendant increased maternal and perinatal morbidities and mortality. It has been hypothesized that leptin contributes immensely to the natural history of pre-eclampsia. However, there is considerable disagreement in the reports of existing research work on the link between fetomaternal serum leptin levels and pre-eclampsia. Objective: To determine and compare the maternal and umbilical cord sera levels of leptin in women with pre-eclampsia and healthy pregnant women. Study design: This is an analytical cross-sectional study. Methods: The study involved consenting 120 pregnant participants (60 on each arm). Pregnant women diagnosed with pre-eclampsia constituted the investigation group, while the controls were normotensive pregnant women. They were matched for maternal age and body mass index. Venous blood specimens were obtained from the participants for assessment of the serum leptin concentration while umbilical cord blood samples were obtained following delivery of the neonate in advance of the removal of the placenta. The collected blood samples were analysed for the levels of leptin in a blinded pattern. The primary outcome measures were maternal serum leptin levels and umbilical cord serum leptin levels. Results: Mean maternal serum leptin concentration in the pre-eclampsia group was significantly higher than that in the control group (24.88 ± 3.92 vs. 15.03 ± 2.98ng/mL, p  < 0.001). Similarly, maternal serum leptin concentration was significantly higher in participants with severe pre-eclampsia compared with those with mild pre-eclampsia (25.91 ± 3.5 vs. 22.83 ± 4.02ng/mL, p  = 0.003). However, the mean umbilical cord serum leptin level in the pre-eclampsia group was significantly lower than in the control group (6.43 ± 2.08 vs. 7.27 ± 2.24; p  = 0.034). There was a weak positive correlation between maternal serum leptin level and neonatal umbilical serum leptin level in the pre-eclamptic group ( r  = 0.21, p  = 0.04). Conclusion: Maternal serum leptin concentration is significantly increased in women with pre-eclampsia, compared with their normotensive counterparts. This increase becomes even more pronounced as the severity of the disease progresses. Maternal serum leptin assessment has the potential to become a veritable tool in the diagnosis and monitoring of pregnancies complicated by pre-eclampsia.